The Behaviour of Cold-Formed stiffened Channels Using ANSYS - Iswisi , Mohamed Ibrahim (Journal of Pure & Applied Sciences, 2019)
In this study, the behavior of cold-formed channels with flange lips and web stiffener steel sections evaluated using the developed technical means. The effect of lateral restraints of purlins of cold-formed sigma sections provided by the roof sheeting is investigated. Finite element analysis software ANSYS is incorporated for calculation to fulfill the accuracy, quickness, and easiness. Uniformly distributed loads are applied on the upper flange of the purlins downward. Connection of roof sheeting to the purlin provided lateral restraints to the purlins. ANSYS software provided a high ability for simulating the model of connection roof sheeting to the purlins. The support type cleat is used to connect purlin to the main beams or the main structure. During the analysis, three types of buckling; local, distortion, and lateral torsion are expected to be explored or at least one of them.The extensive work has been conducted before this study on cold-formed steel purlins and purlin sheeting systems are still few. So the case require many investigations using many and different (various) means to predict the precise response of connecting roof sheeting to purlins. The geometric and material non-linear analyses have performed using ANSYS. In addition, a comparison between the angles of the web stiffeners has conducted. The aim was to evaluate the effect of the lateral restraints on the purlins, and to obtain a new optimal cross-section. During the comparison, the area of the cross-section kept the same for all the elements to obtain the same mass.